ANALISIS PENGARUH KECENDERUNGAN DALAM MENGAMBIL RISIKO DAN PENDIDIKAN KEWIRAUSAHAAN TERHADAP NIAT BERWIRAUSAHA DENGAN EFIKASI DIRI SEBAGAI VARIABEL MEDIASI (Studi pada Mahasiswa Wirausaha Universitas Diponegoro) - Hermawan, Khrisna Akbar; Fitria, Shoimatul (Faculty of Economics and Business Diponegoro University, 2020)
The entrepreneurship rate in Indonesia has actually exceeded international standards, which is 3.1% but Indonesia is still quite behind compared to other countries such as Singapore, Malaysia, Brunei and Thailand. At Diponegoro University itself, the entrepreneurship rate of students is quite high, but in the last three years experienced volatility in the number of entrepreneurial students. The majority of Diponegoro University graduates still choose to find employment rather than providing employment. Even though Indonesia will soon experience a demographic bonus that will be dominated by millennials, where in several other studies involving millennials, it is stated that the majority of millennials want to become entrepreneurs. For this reason, this study discusses how the relationship between entrepreneurial intentions with entrepreneurship education and the propensity to take risks and how the effect of self-efficacy in mediating the relationship between entrepreneurial intentions and entrepreneurship education among students at Diponegoro University. The population in this study were all entrepreneurial students at Diponegoro University who took samples with a purposive sampling technique to obtain 120 respondents who participated in this study. The questionnaire was tested first using the instrument in the form of feasibility studies to test the validity and reliability testing. The analytical method of this research uses Structural Equation Modeling (SEM) analysis with AMOS 24.0 analysis tools. The processing results of the SEM analysis in this study showed that the propensity to take risk of a positive and significant effect on entrepreneurial intentions. Then, entrepreneurship education also has a positive and significant effect on entrepreneurial intentions. Furthermore, entrepreneurship education through self-efficacy is also able to positively and significantly influence entrepreneurial intentions. Self-efficacy variable was found to have a dominant influence on entrepreneurial intentions so important for entrepreneurial students to have the confidence and the ability or willingness to continue to learn things related to entrepreneurship.